"Končno besedo bo izrekla zgodovina" - Guček, Boštjan (Acta ecclesiastica Sloveniae, 2024)
This article presents the priests Jože Gregorič (1908–1989) and Alojzij Kozar (1910–1999) and their correspondence preserved in the personal archives of both clergymen. Their letters have not yet been published, so it is our hope that this article will speed up their path to be raised to the Altar while simultaneously fulfilling the task set by the founders of this publication to present to the wider public sources for church history.
Keywords: correspondence; Gregorič, Jože; Kolar, Bogdan; korespondenca; Kozar, Alojzij